The Global Youth Tobacco Survey: 2001–2002 in Riyadh region, the Kingdom of Saudi Arabia - Al-Bedah AM; Qureshi NA (Dove Medical Press, 2011)
Abdullah Mohammed Al-Bedah1, Naseem Akhtar Qureshi21Arabian Center for Tobacco Control, 2General Administration for Medical Research and Mental Health and Social Services, Ministry of Health, Riyadh, Saudi ArabiaBackground: Tobacco use is a major public health problem, and its prevalence is globally increasing, especially among children and adolescents.Objective: The Global Youth Tobacco Survey aimed to explore the epidemiological trends and risk factors of tobacco smoking among intermediate school boys in Riyadh region of the Kingdom of Saudi Arabia.Method: A two-stage cluster sample design was used to produce a representative sample of male students from selected schools. The participants (n = 1830) self recorded their responses on the Global Youth Tobacco Survey questionnaire.Results: Lifetime prevalence of cigarette smoking was 35%, while 13% of students currently used other tobacco products. About 16% of students currently smoked at home, and 84% of students bought cigarettes without any refusal from storekeepers. Thirty-one percent and 39% of students were exposed to secondhand tobacco smoke inside and outside the house, respectively, which was definitely or probably harmful to health as opined by 87% of participants, and 74% voiced to ban smoking from public places. Among current smokers, 69% intended (without attempt) to quit and 63% attempted (but failed) to quit during the past year. Almost an equal number of students saw antismoking and prosmoking media messages in the last month, and 28% of students were offered free cigarettes by a tobacco company representative. In schools, more than 50% of students were taught about the dangers of cigarette smoking in the last year. Smoking by parents, older brothers, and close friends, watching prosmoking cigarette advertisements, free offer of cigarettes by tobacco company representatives, perception of smoking being not harmful, and continuing smoking which can be easily quit significantly increased the odds of smoking by students.Conclusion: The common use of tobacco in school populations needs to be addressed by, among other tobacco control measures, a strict ban on cigarette selling to minors and intensive regular tobacco control campaigns involving health and religious messages.Keywords: tobacco use, secondhand tobacco smoke, environmental tobacco smoke, intermediate school boys, Global Youth Tobacco Survey, Saudi Arabia